Development of GKM Workspace Application - Hafizah Hanim; Ullya Mega Wahyuni; Hafid Dwi Adha; Lova Endriani Zen (SEULANGA SYSTEM PUBLISHER, 2025)
At the department level, the Quality Control Group (GKM) is an extension of the Quality Assurance Institution. Implementing the Internal Quality Assurance System (SPMI) within the department is GKM's primary responsibility. With reference to the National Higher Education Standards (SN Dikti) and international quality assurance (IQA), the SPMI policy seeks to be a commitment of higher education institutions to sustainably maintain and improve the quality of higher education providers in order to fulfill the vision and mission and satisfy stakeholders through the application of the Tridharma of higher education. In the PPEPP cycle (Determination, Implementation, Evaluation, Control, Improvement), GKM is crucial to maintaining quality standards. GKM keeps an eye on and assesses every application of quality standards. However, the GKM Team has not been able to perform its duties as effectively as they could in its implementation. The restricted amount of time and teams available is one of the causes. This study is to support the GKM's responsibilities, particularly with regard to monitoring and assessment. in order for GKM to perform its tasks more readily, effectively, and efficiently while saving time. The